ISLAM DAN PROBLEMATIKA KEMISKINAN - Wijaya, Padma; Prakoso, Dicky Dwi; Hadi, Abdul; Syahrullah, Syahrullah (Asosiasi Dosen PTKIS Indonesia, 2025)
Poverty is a complex structural problem and remains a major challenge in Indonesia, a country with a Muslim majority. From an Islamic perspective, poverty is not only an economic issue, but also includes social and moral dimensions. Islam offers an integral solution through the concept of zakat, infaq, sedekah, and waqf which function as instruments of wealth distribution and social solidarity. This article aims to examine the problem of poverty in Indonesia from an Islamic perspective and examine the role of Islamic values and institutions in overcoming it. Using a literature study method and a qualitative approach, this study found that although Islamic teachings have great potential in poverty alleviation, implementation in the field still faces obstacles, such as low zakat literacy, less than optimal institutions, and regulatory challenges. Therefore, integration between Islamic values and sustainable public policies is needed to effectively overcome poverty in Indonesia.